Revitalizing flood-prone areas through socio-environmental strategies: A qualitative approach to urban flood management - Pamungkas, Paminto Jati; Kristianto, Ary; Prianto, Muhammad Dwi; Rahman, Robby Zidni; Firmansyah, Risky Teguh (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The Ciliwung River is one of the most important rivers in Tatar Pasundan, especially because it passes through the capital city of DKI Jakarta and often causes annual floods in its downstream areas. The length of this river reaches almost 120 km and passes through several areas, including Bogor Regency, Bogor City, Depok City, and DKI Jakarta Province. High rainfall is one of the factors that often causes flooding in areas around rivers. Methods: This research aims to analyze the management of flood disasters that occur due to the overflow of the Ciliwung River. The analysis carried out by the author used qualitative methods with a literature review. Findings: The results obtained from the literature review of several journals, namely flood management on the Ciliwung River, cannot still be said to be completely successful. This is because several factors trigger floods that have not yet been resolved and appropriate solutions are needed for flood-prone areas so that they can be revitalized so that they can provide direct benefits to the community. Conclusion: The study highlights the persistent challenges in managing flood disasters caused by the overflow of the Ciliwung River. Despite various efforts, flood management in the Ciliwung River Basin has not been entirely successful. Several unresolved factors continue to trigger flooding, indicating the need for more effective and sustainable solutions. The revitalization of flood-prone areas is essential to mitigate the impact and provide direct benefits to the affected communities. Novelty/Originality of the Article: Unlike previous studies that focus on specific technical solutions, this research highlights the need for holistic revitalization of flood-prone areas, considering socio-environmental factors to enhance community resilience and sustainable flood mitigation strategies.